(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: The central sulcus, which is located between the primary motor and primary somatic sensory cortex is an important structure and landmark of the cerebral hemisphere. Morphology of the central sulcus varies with age, sex, manual skill, handedness and in many diseases. This study is carried out to establish a normal standard in different age groups in length and depth of the central sulcus. Materials and Methods: A cross-sectional, analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, on one hundred and forty (140) on human cerebral hemispheres. The samples were divided into four different age groups i.e. Group A (20-29 years), Group B (30-39 years), Group C (40-49 years) and Group D (50-59 years). All the samples were studied morphologically. Results: The mean length of central sulcus was 102.89±3.55 mm to 96.83±3.92 mm in male and 98.00±5.17 mm to 96.29±2.56 mm in female. Depth of the central sulcus was 20.02±2.41 mm to 21.50±2.21 mm in male and 20.50±2.57 mm to 21.36±1.87 mm in female. The difference in mean length of the right central sulcus between male and female was statistically significant in group A (p<0.05) and B (p<0.05). The difference in mean depth of the central sulcus between male and female was not statistically significant in any age groups. No significant difference was found between right and left hemisphere for both length and depth of the central sulcus. The difference in mean length and depth of the central sulcus between different age groups for both left and right hemisphere was not statistically significant in any age group. Conclusion: The length and depth of the central sulcus showed gradual decreasing values with advancing age. DOI: http://dx.doi.org/10.3329/bja.v11i1.20504 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 19-24